Static Stress Analysis and Fatigue Life Prediction of Rocket Motor Test Stand Using Numerical Simulation - Lasinta Ari Nendra Wibawa (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2021)
The rocket motor test stand is the equipment used to test the rocket motor's performance under controlled conditions. This equipment is used to measure the thrust of the Dextrose rocket motor and test the ability of components such as the tube, fuel, nozzle and cap of the rocket itself. Before the Dextrose rocket flight test is carried out, it must go through this test. In this study, the variations in the thrust are 2000, 2250, 2500, 2750, and 3000 N. The rocket motor test stands used Aluminum 6063-T6 which has light density and medium strength. Numerical simulations were carried out with Ansys Workbench software using the finite element method. The results of the static stress analysis show that the greater the thrust, the greater the maximum von Mises stress and deformation. It is inversely related to the safety factor. The greater the thrust, the lower the safety factor of the rocket motor test stand. The results of the fatigue simulation show that the greater the thrust, the lower the prediction of fatigue life and the safety factor. Rocket motor test stand fails to reach a 1 million cycle life at 3000 N thrust.